2004
DOI: 10.1177/009286150403800411
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Practitioners’ Uptake of a Secondary Care-Based Medicines Information Service in the United Kingdom

Abstract: The purpose of this study was to determine the extent to which primary care practitioners (doctors and nurses) use a secondary care-based medicines information service and to discover how nonusers of the service answer medicine-related inquiries. A self-administered mail survey was distributed to the target population from three primary care trusts (a primary care trust is responsible for all healthcare needs of its geographically bound population; on average, each primary care trust covers 170,000 people) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…This may reflect the available sources they have to deal with medicine‐related enquiries. Studies have shown that doctors access reference sources such as the British National Formulary and the Medicines Compendium Summary of Product Characteristics (SmPCs) 7 . Given that these two reference sources were most used by pharmacists in this study, and over 80% ( n = 53/64) of responses were categorised as green, perhaps doctors should be encouraged to refer more enquiries to the community pharmacist, and in so doing free their time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may reflect the available sources they have to deal with medicine‐related enquiries. Studies have shown that doctors access reference sources such as the British National Formulary and the Medicines Compendium Summary of Product Characteristics (SmPCs) 7 . Given that these two reference sources were most used by pharmacists in this study, and over 80% ( n = 53/64) of responses were categorised as green, perhaps doctors should be encouraged to refer more enquiries to the community pharmacist, and in so doing free their time.…”
Section: Discussionmentioning
confidence: 96%
“…However, little research has been conducted to determine the nature of medicine‐related questions that community pharmacies handle, nor the validity of the responses 6 . Research data relating to medicine call handling seem to be limited to specialist services 7 or national drug information centres 8 …”
Section: Introductionmentioning
confidence: 99%
“…GPs formed a lower proportion of users. Research shows that, even when GPs are aware of UKMi services, many do not use them because they lack understanding of what they offer [47] or maybe because they seek advice from community or practice pharmacists, or prescribing advisors. We did not investigate why HPs were motivated to contact the NWMi Centre, but it has been shown that a need for independent evidence‐based information and lack of time and skills in accessing and appraising information can prompt prescribers to contact medicines information services [48] …”
Section: Discussionmentioning
confidence: 99%
“…This may involve creation of centralized drug databases, input into creation of local formularies and prescribing policies, and assessment of new drugs, as well as advising on use of medicines for particular patients. Such services have been shown to have a direct and beneficial impact on patient care in providing information on adverse drug effects (Stubbington, Bowey, Hands, & Brown, 1998) but evidence of more general impact is limited (Hands, Stephens, & Brown, 2002; Rutter, Brown, & Rutter, 2004).…”
Section: Pharmaceutical Information Producers and Usersmentioning
confidence: 99%